Vivienda colectiva, la reinterpretación del inquilinato en la localidad de Los Mártires Bogotá para las mujeres trabajadoras sexuales y sus familias. (2022)
The project seeks to be an innovative space, starting from what is currently a tenancy that does not have attractions beyond its economic price. This prototype of housing proposes to extract the best of the tenancies and the essence of a traditional and communal housing, brought to the new needs and seeking to solve deficiencies that produce the most significant problems of the tenancy that is unhealthiness, overcrowding and insecurity. Similar projects are not presented, since we found projects with only one of the characteristics that the project meets. The tenancy is presented as nothing more than a dwelling, and we find training and child protection equipment but not included in the dwelling. A comprehensive project is proposed that provides facilities for women sex workers and new life opportunities for those who so wish, in addition to caring for their children, which is usually their greatest concern.